Prediction of biochemical recurrence in prostate cancer patients who underwent prostatectomy using routine clinical prostate multiparametric MRI and decipher genomic score. Issue 4 (30th September 2019) - Jambor, Ivan; Falagario, Ugo; Ratnani, Parita; Perez, Ileana Montoya; Demir, Kadir; Merisaari, Harri; Sobotka, Stanislaw; Haines, George K.; Martini, Alberto; Beksac, Alp Tuna; Lewis, Sara; Pahikkala, Tapio; et al.
Abstract : Background: Biochemical recurrence (BCR) affects a significant proportion of patients who undergo robotic‐assisted laparoscopic prostatectomy (RALP). Purpose: To evaluate the performance of a routine clinical prostate multiparametric magnetic resonance imaging (mpMRI) and Decipher genomic classifier score for prediction of biochemical recurrence in patients who underwent RALP. Study Type: Retrospective cohort study. Subjects: Ninety‐one patients who underwent RALP performed by a single surgeon, had mpMRI before RALP, Decipher taken from RALP samples, and prostate specific antigen (PSA) follow‐up for >3 years or BCR within 3 years, defined as PSA >0.2 mg/ml. Field Strength/Sequence: mpMRI was performed at 27 different institutions using 1.5T ( n = 10) or 3T scanners and included T2 w, diffusion‐weighted imaging (DWI), or dynamic contrast‐enhanced (DCE) MRI. Assessment: All mpMRI studies were reported by one reader using Prostate Imaging Reporting and Data System v. 2.1 (PI‐RADsv2.1) without knowledge of other findings. Eighteen (20%) randomly selected cases were re‐reported by reader B to evaluate interreader variability. Statistical Tests: Univariate and multivariate analysis using greedy feature selection and tournament leave‐pair‐out cross‐validation (TLPOCV) were used to evaluate the performance of various variables for prediction of BCR, which included clinical (three), systematic biopsy (three), surgical (six: RALP Gleason Grade Group [GGG], extracapsular extension, seminal vesicle invasion, intraoperative surgical margins [PSM], final PSM, pTNM), Decipher (two: Decipher score, Decipher risk category), and mpMRI (eight: prostate volume, PSA density, PI‐RADv2.1 score, MRI largest lesion size, summed MRI lesions' volume and relative volume [MRI‐lesion‐percentage], mpMRI ECE, mpMRI seminal vesicle invasion [SVI]) variables. The evaluation metric was the area under the curve (AUC). Results: Forty‐eight (53%) patients developed BCR. The best‐performing individual features with TLPOCV AUC of 0.73 (95% confidence interval [CI] 0.64–0.82) were RALP GGG, MRI‐lesion‐percentage followed by biopsy GGG (0.72, 0.62–0.82), and Decipher score (0.71, 0.60–0.82). The best performance was achieved by feature selection of Decipher+Surgery and MRI + Surgery variables with TLPOCV AUC of 0.82 and 0.81, respectively Data Conclusion: Relative lesion volume measured on a routine clinical mpMRI failed to outperform Decipher score in BCR prediction. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2020;51:1075–1085.